The Effect of Work From Home (WFH) on Employee Performance through the Work-Life Balance (WLB) During the Covid-19 Period - Nur Husnul Khotimah; Sumardi Sumardi; Ria Mardiana Yusuf (Magister Management, Hasanuddin University, 2021)
The Athirah Islamic School Foundation in Makassar is one of the institutions owned by Kalla Group that implement Work From Home (WFH) due to the Covid-19 Pandemic. Different from working from the office, the nature of work from home cause the imbalance between work and personal life (work-life balance) and also leads to an impact on employee performance. This study aims to prove the effectiveness of work from home on employee performance through the work-life balance of employees of the Athirah Islamic School Foundation in Makassar. This study was conducted in path analysis, where 75 employees taken as samples from 297 populations at the Athirah Islamic School Foundation in Makassar. The sampling technique used the proportionate stratified random sampling method. The data were collected by using interviews and questionnaires and then analyzed by using SPSS 20 version. This research shows that work from home has a positive and significant effect on employee performance. Work from home has a positive and significant effect on work-life balance. Work-life balance has a positive and significant effect on employee performance. Meanwhile, work from home has a positive and significant effect on employee performance through the work-life balance.